„Ein Unbekanntes ist nur der Geschmack“: zu Levin Ludwig Schückings literatursoziologischem Ansatz - Schell, Sandra; Venzl, Tilman (Internationales Archiv für Sozialgeschichte der deutschen Literatur, 2021)
The article reconstructs Levin Ludwig Schücking’s History of Taste as a method of writing literary history. Moreover, it lays out, for the first time, the cultural and literary-political dimensions of his approach by considering the context of the history of literary studies comprehensively. The article demonstrates how Schücking refers to sociology in a twofold manner: as a way of scholarly thinking that is related to certain methodological techniques, and as a way to overcome the “crisis of modernity” manifested in the rift between authors and readers in literary life.